2016
DOI: 10.1590/1983-40632016v4640810
|View full text |Cite
|
Sign up to set email alerts
|

Phosphite and phosphate in the accumulation and translocation of nutrients in common bean1

Abstract: Although used as an additional nutritional source of phosphorus in agriculture, little is known about the effects of phosphites on plants. In order to evaluate the influence of phosphite and phosphate on the accumulation and translocation of phosphorus and cationic nutrients, in common bean, three experiments were conducted. In the first experiment, five concentrations (0.5 mg L-1, 10 mg L-1, 20 mg L-1, 30 mg L-1 and 60 mg L-1) were studied in a nutrient solution combined with two forms of phosphorus [phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…However, our study did not explicitly demonstrate the defense mechanisms activated by potassium phosphite in potato plants. Besides the potential inhibitory impact on disease development, there are many proven beneficial effects of phosphites on crops [64][65][66]. A study conducted by Tambascio et al [67] showed that the application of KPhi to seed tubers resulted in early plant growth by reducing the period between planting and emergence, and increasing leaf area, dry-matter, and mycorrhizal colonization in potatoes under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study did not explicitly demonstrate the defense mechanisms activated by potassium phosphite in potato plants. Besides the potential inhibitory impact on disease development, there are many proven beneficial effects of phosphites on crops [64][65][66]. A study conducted by Tambascio et al [67] showed that the application of KPhi to seed tubers resulted in early plant growth by reducing the period between planting and emergence, and increasing leaf area, dry-matter, and mycorrhizal colonization in potatoes under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moor et al (2009) encontraron que cuando se emplea Phi en la fertilización de fresas no se produce una disminución del crecimiento, pero tampoco se produce un aumento del rendimiento con respecto a la fertilización tradicional con Pi. Araujo et al (2016) señalan que, en frijol común, en condiciones de deficiencia de P, el Phi suministrado con la solución nutritiva ocasiona una disminución de la acumulación de P. Por otra parte, López-Arredondo y Herrera-Estrella (2012) encuentran que plantas transgénicas capaces de expresar el ptxD de Pseudomonas stutzeri precisan entre un 30 y un 50 % menos de P cuando son fertilizadas con Phi que cuando son fertilizadas con Pi. Todo ello ha motivado la realización de este ensayo, donde se ha estudiado el efecto que la presencia (1 mmol L -1 ) o ausencia de Phi (0 mmol L -1 ) tiene sobre el crecimiento y la concentración foliar de macro y micronutrientes de plantas de tomate cultivadas con diferentes niveles de Pi (0.05, 1.00 y 2 mmol L -1 ).…”
Section: Introductionunclassified